No meio do caminho: os processos de criação e cuidado de uma criatura sem nome no território-dos-nomes-que-grudam - Barros, Jialu Fernandes Pombo de (2022)
Taking as a departure point our experience as a psi clinic patient, we developed a transdisciplinary research in the fields of both Clinical Psychology and Art, addressing possible crossroads between processes of creation and care through integrative perspectives towards life and its surroundings found both in philosophical, theoretical approaches and in care practices such as those named by the Unified Health System (SUS) in Brazil as Integrative Complementary Health Practices (PICS). In this way, we attempt to propose intensive exits that might allow us to leave aside perspectives structured under a regime of existential schism that conceive the body and mind of living beings as two separate entities and produces dualistic views, a regime which we call “the territory-of-the-glued-names”. Identifying that this regime uses verbal/intelligible language as a tool for its maintenance, the research also focuses on our relation with systems of naming and social categorization. We address especially categories concerning gender expressions and categories concerning a diversity of existential conditions often considered to be inadequate due to their particular ways of acquiring language and expressing themselves. Understanding that the bodies themselves already constitute a form of expression, we expand the notions through which the term "language" is usually understood, both in the clinical practice and in the common sense. By dwelling into creative experiments by different authors, we outline examples of how unimpeded languages germinating from care processes might potentially become tools able to transform the very processes from which they emerged. Remembering that life happens in acts of creation, and that, therefore, to create is to live, we propose clinical practices that establish horizontal relationships, in which the creation of unique expressions of each patient might become the master key to care processes that happen midway through the path of a single-life in all its integrality with the biosphere and the cosmos